Neurological manifestation of coeliac disease with particular emphasis on gluten ataxia and immunological injury: a review article - Osman, Dina (Gastroenterol Hepatol Bed Bench, 2021)
Coeliac disease (CD) is a gluten-induced enteropathy affecting 1% of the population and has extra intestinal manifestations. One such expression involves nervous system, and CD may present as gluten ataxia (GA), peripheral neuropathy and epileptiform disorder among others. Considerable controversy exists on the exact pathophysiological mechanism of gluten leading to ataxia. It is, however, clear that in intestinal axis tissue transglutaminase 2 (tTG2) is the primary target but in the nervous system, tTG6 may be the causative antigen although its exact role is not clear. Furthermore, it has also been postulated that anti-gangliodise antibodies may play a role in the emergence of central pathology if not the key contender. Moreover, the association of neurological injury with non-coeliac gluten sensitivity (NCGS), a related but pathologically different condition implies an independent mechanism of neuronal injury by gluten in the absence of CD. This review will touch on the salient features of CD and the nervous system and will highlight current controversies in relation to gluten and GA.